О принципах когнитивно-риторического анализа публицистического дискурса - Лассан, Э. Р. (Kalbotyra, 1994)
The article suggests a new method of discourse analysis – the cognitive-rhetoric method. The material of our investigation is social-political texts of the 60th connected with Danyel-Syniavsky process.The text is represented as a structure based on the binary oppositions of ideas. These oppositions have a scope to develop to conceptual metaphors. The last point of analysis is provision with words depending on the features of an addresse.